2000
DOI: 10.1034/j.1600-0412.2000.079004293.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of usefulness of estradiol vaginal tablets and estriol vagitories for treatment of vaginal atrophy

Abstract: Estradiol vaginal tablets provides an effective alternative to traditional forms of local estrogen therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Ten studies reported endometrial biopsy findings. 31,32,34,38,40,42,4448 Among patients with an intact uterus (during and up to 1 year of vaginal estrogen use), endometrial pathology was rarely abnormal; this consisted of two cases of hyperplasia with atypia in a study of 165 participants (1.2%) followed for 12 weeks; one received an estradiol vaginal ring and the other estriol cream. 34 Differences in serum estradiol levels were not identified between various estrogen delivery mechanisms with the exception of one study comparing the 25-microgram estradiol vaginal tablet to 1.25 mg conjugated estrogen cream daily (ie, 2 g cream daily); a higher percentage of the patients given this conjugated estrogen cream dose had serum estradiol levels above postmenopausal norms.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies reported endometrial biopsy findings. 31,32,34,38,40,42,4448 Among patients with an intact uterus (during and up to 1 year of vaginal estrogen use), endometrial pathology was rarely abnormal; this consisted of two cases of hyperplasia with atypia in a study of 165 participants (1.2%) followed for 12 weeks; one received an estradiol vaginal ring and the other estriol cream. 34 Differences in serum estradiol levels were not identified between various estrogen delivery mechanisms with the exception of one study comparing the 25-microgram estradiol vaginal tablet to 1.25 mg conjugated estrogen cream daily (ie, 2 g cream daily); a higher percentage of the patients given this conjugated estrogen cream dose had serum estradiol levels above postmenopausal norms.…”
Section: Resultsmentioning
confidence: 99%
“…In general, when compared with vaginal estrogen creams or suppositories, tablets provide a more consistent dose of the hormone, reduce potential leakage, and are associated with greater patient adherence 6,7. All treatments provided equivalent relief of the symptoms of VVA based on composite scores of vaginal symptoms (dryness, soreness, and irritation).…”
Section: Introductionmentioning
confidence: 99%
“…In a Cochran Review evaluating local estrogen therapy for vaginal atrophy, data were extracted from 19 studies in 4162 menopausal women involving vaginal rings, creams, tablets, and gels (56). All estrogen products studied appeared to be equally effective for relief of the symptoms of vaginal atrophy (29,37,62–73). Secondary outcome analysis in many of these studies also showed acidification of the vaginal pH and an increase in the VMI in favor of mature squamous cells.…”
Section: Hormonal Therapies For Atrophic Vaginitismentioning
confidence: 99%